Masyarakat Rao di Malaysia dan Perak (Tanjung Malim) - Fathil, Fauziah (2018)
The paper highlights the history of migration of Rao(Rawa) people from West Sumatra, Indonesia to Malay Peninsula. Starting with the origin of the Rao people and the political history of Rao in the Sumatran Island, the paper then deals with various contributory factors for the Rao migration to the Malay Peninsula which saw a great influx of Rao migrants to Malay states especially from 18th century until early 20th century. The paper also discusses the roles and contributions of the Rao community in the socio-economic developments and politics of the Malay Peninsula.